Determinants of Learning Motivation for Students of Class of 2020 Culinary Management Concentration, Padang State University - Yulias, Yahya Aulia; Andriani, Cici; Gusnita, Wiwik; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This research was motivated by the change in learning patterns to online, which had an impact on the 2020 Class of Family Welfare Education students at Padang State University. This research aims to analyze the influence of online learning patterns on student learning motivation and perceptions. The research method uses a quantitative approach with simple linear regression analysis and hypothesis testing, as well as interviews for qualitative data. The research results show that the online learning pattern is in the medium category with several technical and interaction obstacles. There is a significant and positive influence of online learning patterns on student learning motivation (Y = 11,868 + 0,308X, tcount 5,989 > ttable 1,99547). Student perceptions tend to be positive, even though they face adaptation challenges. In conclusion, online learning has a positive impact on learning motivation and is well received by students, but it still requires the development of infrastructure and learning methods to optimize the educational process in the field of culinary arts and family welfare.